Step-interviews: an artist's book in displacements through the city (Palíndromo, 2023)
This article revisits the method of step-interviews, which gave rise to the artist book Cidade Passo, years after its publication, proposing a re-reading that shifts the work from its initial approach to ethnography towards the notion of education of attention. In developing this analysis, I relate the step-interviews to the image of "string figures" proposed by Donna Haraway to think collaborative systems among living beings and the notion of the footpath as design and architectural object, based on the reflections of Jacques and Careri. Finally, I rewrite one of the experiences made in the context of the book production in São Paulo, and propose a dialogue of this with a new trail, made in 2020, this time in Salvador, using a mode of writing in first person that identifies with the notion of "f(r)iccional academic writing".
Keywords: walking interview; ethnography; education; art; transdisciplinarity